2023
DOI: 10.1007/s11897-023-00600-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Right Ventricular Function—a State of the Art

Abstract: Purpose of Review The right ventricle (RV) has a complex geometry and physiology which is distinct from the left. RV dysfunction and failure can be the aftermath of volume- and/or pressure-loading conditions, as well as myocardial and pericardial diseases. Recent Findings Echocardiography, magnetic resonance imaging and right heart catheterisation can assess RV function by using several qualitative and quantitative parameters. In pulmonary hypertension (PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 175 publications
0
2
0
Order By: Relevance
“…In order to ensure the best possible treatment of CS and the most optimal Impella support, appropriate monitoring of RV function appears to be essential [ 25 , 26 , 27 ]. Josiassen et al recently showed that the LV Impella can benefit RV function in cases of myocardial infarction-related CS in pigs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure the best possible treatment of CS and the most optimal Impella support, appropriate monitoring of RV function appears to be essential [ 25 , 26 , 27 ]. Josiassen et al recently showed that the LV Impella can benefit RV function in cases of myocardial infarction-related CS in pigs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to assessing the function of the left ventricle, it is also important to assess the right ventricle (estimation of its size, systolic excursion of the tricuspid annulus-TAPSE, etc.) [173]. A significant reduction in right ventricular function is a powerful predictor of death and the need for heart transplantation in patients with proven myocarditis [46].…”
Section: Echocardiographymentioning
confidence: 99%